Analysis of Epizootiological-Epidemiological Situation on Brucellosis in the Russian Federation in 2018 and Forecast for 2019 - D. G. Ponomarenko; E. B. Ezhlova; D. V. Rusanova; A. A. Khachaturova; N. D. Pakskina; T. V. Berdnikova; E. A. Manin; O. V. Semenko; O. V. Logvinenko; E. L. Rakitina; M. V. Kostyuchenko; O. V. Maletskaya; et al. (Проблемы особо опасных инфекций, 2019)
Presented is the analysis of brucellosis incidence among humans and animals in the Russian Federation in 2018. Epizootiological situation in the regions of developed animal husbandry remains reasonably tense. In 2018, as in previous years, the foci of bovine cattle and small ruminant brucellosis were registered in the North Caucasian, Southern Federal Districts, Volga and Siberian Federal Districts, the share of which made up to more than 90% of all registered in Russia potentially hazardous as regards brucellosis areas and cases of the disease in animals. Against the background of long-term unfavorable epizootic condition, the incidence of brucellosis over the past three years was, on average, 14 % lower than the average long-term indicators. The greatest number of cases (94.1 % of the overall Russian incidence) is registered in the administrative subjects of the North Caucasus Federal District, Southern Federal District and Siberian Federal District, which have the maximum levels of brucellosis incidence in cattle (88.9 %) and small ruminants (95 %). In 2019, persistence of epidemiological problems in regard to brucellosis in the subjects of the North Caucasus Federal District (primarily the Republic of Dagestan, Stavropol Territory), the Southern Federal District (the Republic of Kalmykia, Volgograd and Astrakhan Regions), and the Siberian Federal District (the Tuva Republic, the Omsk and Tyumen Regions) is predicted. The number of human cases of brucellosis may be within the range of 290–310 cases (intensive incidence rate per 100 thousand population – 0.21).